Mitoxantrone treatment in a patient with multiple sclerosis and pattern III lesions. Issue 3 (3rd June 2018) - Grüter, Thomas; Metz, Imke; Gahlen, Anna; Kneiphof, Janina; Stork, Lidia; Brück, Wolfgang; Gold, Ralf; Kleiter, Ingo
Abstract: Background: Brain biopsies of multiple sclerosis patients identified three intraindividually stable lesion patterns. Apart from beneficial effects of plasma exchange in patients with type II lesions, little is known about how multiple sclerosis lesion histology could guide therapeutic decisions. Case presentation: Here, we report on a 53‐year‐old male patient with polysymptomatic cerebral syndrome as the first episode of multiple sclerosis. Brain biopsy showed an inflammatory demyelinating lesion with apoptotic oligodendrocytes and a loss of myelin‐associated glycoprotein, pathological features typical for pattern III lesions. High‐dose steroids and immunosuppressive treatment with mitoxantrone led to a substantial improvement of disability and long‐term clinical stability. Conclusion: Mitoxantrone therapy along with steroid pulses could potentially be considered as a therapeutic option for pattern III lesions. Abstract : Here, we report on a 53‐year‐old male patient with polysymptomatic cerebral syndrome as first episode of MS with pattern III lesions. High‐dose steroids and immunosuppressive treatment with mitoxantrone led to a substantial improvement of disability and long‐term clinical stability.